Evaluation of auditory system in vitiligo patients: A case-control study - Sima Tajik; Kosar Nazary; Azar Shirzadian Kebria; Keyvan Kiakojori (Elsevier, 2024)
Background: Vitiligo is a common acquired pigmentary disorder characterized by well-defined areas of depigmentation due to loss of melanocytes. Vitiligo can affect melanocytes in the auditory system and potentially hearing. Objective: The aim of this study was to investigate hearing changes in vitiligo patients. Methods: Twenty-six with vitiligo patients and 26 demographically matched healthy controls were included in this study. Audiological function was evaluated using pure tone audiometry (PTA), speech audiometry and tympanometry tests in all subjects. Results: The mean hearing threshold of the left ear at frequencies of 250 and 8000 Hz in vitiligo patients was significantly higher than the control group. Sensorineural hearing loss (SNHL) was seen in 14 (53.8 %) vitiligo patients and 5(19.2 %) control group (p < 0.05). Most affected patients (10/14; 71 %) had bilateral hearing loss especially in high frequency (8000 Hz). A significant association was identified between vitiligo and SNHL (OR 4.9; 95 % CI, 1.41-16.98, P = 0.01). There was a statistically significant correlation between hearing impairment and age in both groups. Gender, severity, activity and duration of vitiligo had no a significant effect on the results of audiometric tests. Conclusion: This study confirmed that the auditory system was affected in vitiligo patients. Vitiligo patients might be at a higher risk for auditory abnormalities at a younger age than control subjects. Auditory evaluation of vitiligo patients should be considered for early detection of hearing loss.